Eurycomanone suppresses expression of Lung Cancer Cell Tumor Markers, prohibitin, annexin 1 and endoplasmic reticulum protein 28 - Wong, P.F.; Cheong, W.F.; Shu, M.H.; Teh, C.H.; Chan, K.L.; AbuBakar, Sazaly (2012)
Bioactive compounds from the medicinal plant, Eurycoma longifolia Jack have been shown to promote anti-proliferative effects on various cancer cell lines. Here we examined the effects of purified eurycomanone, a quassinoid found in Eurycoma longifolia Jack extract, on the expression of selected genes of the A549 lung cancer cells. Eurycomanone inhibited A549 lung cancer cell proliferation in a dose-dependent manner at concentrations ranging from 5 to 20 mu g/ml. The concentration that inhibited 50 of cell growth (GI(50)) was 5.1 mu g/ml. The anti-proliferative effects were not fully reversible following the removal of eurycomanone, in which 30 of cell inhibition still remained (p < 0.0001, T-test). At 8 mu g/ml (GI(70)), eurycomanone suppressed anchorage-independent growth of A549 cells by >25 (p < 0.05, T-test, n = 8) as determined using soft agar colony formation assay. Cisplatin, a chemotherapy drug used for the treatment of non small cell lung cancer on the other hand, inhibited A549 cells proliferation at concentrations ranging from 0.2 mu g/ml to 15 mu g/ml with a GI(50) of 0.58 mu g/ml. The treatment with eurycomanone reduced the abundance expression of the lung cancer markers, heterogeneous nuclear ribonucleoprotein (hnRNP) A2/B1, p53 tumor suppressor protein and other cancer-associated genes including prohibitin (PHB), annexin 1 (ANX1) and endoplasmic reticulum protein 28 (ERp28) but not the house keeping genes. The mRNA expressions of all genes with the exception of PHB were significantly downregulated, 72 h after treatment (p < 0.05, T-test, n = 9). These findings suggest that eurycomanone at viable therapeutic concentrations of 5-20 mu g/ml exhibited significant anti-proliferative and anti-clonogenic cell growth effects on A549 lung cancer cells. The treatment also resulted in suppression of the lung cancer cell tumor markers and several known cancer cell growth-associated genes. (C) 2011 Elsevier GmbH. All rights reserved.